Almost sure asymptotic stability for some stochastic partial functional integrodifferential equations on Hilbert spaces. Issue 1 (1st January 2019) - Dieye, Moustapha; Diop, Mamadou Abdoul; Ezzinbi, Khalil
Abstract: In this work, we study the asymptotic behavior of the mild solutions of a class of stochastic partial functional integrodifferential equation on Hilbert spaces. Using the stochastic convolution developed, we establish the exponential stability in p − mean square with p ≥ 2 . Also, pathwise exponential stability is proved for p > 2. We extend the result of an example is provided for illustration.